Pelatihan Menulis Pantun Berbasis Kearifan Lokal di SMP Negeri 1 Muaro Jambi - Mestika Putra, Yoga; Triandana, Anggi; Fitriah, Siti; Putri, Aprilia Kartika; Amri, Ulil (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2024)
Pantun is an old form of literary work that still survives today. Uniquely, pantun can be used in formal and non-formal events. However, among students, especially junior high school (SMP) students, writing pantun is still something that is difficult to do. Students have difficulty developing their ideas due to a lack of guidance in writing pantun well. The Community Service Team (PKM) of the Indonesian Literature Study Program at Jambi University held pantun writing training aimed at helping students, especially in writing old poems in the form of pantun. The training held by the PKM team is a rhyme writing training aimed at junior high school students who are in the teenage age group. It is hoped that this activity held for students of SMP N 1 Muaro Jambi can provide motivation and help them preserve Malay culture through pantun. The results of local wisdom-based pantun writing training activities carried out at SMP N 1 Muaro Jambi went smoothly. As students gain a comprehensive understanding of pantun from theory to practice.